1979
DOI: 10.1007/bf02586911
|View full text |Cite
|
Sign up to set email alerts
|

A new concept of the anatomy of the anal sphincter mechanism and the physiology of defecation

Abstract: The pathology of anal fistulas was studied in 300 patients and a simple classification is put forward. Two main types of fistula are recognized: intrasphincteric and extrasphincteric, according to the relation of the track to the external sphincter. All fistulas start as a central space infection which either remains confined to the intrasphincteric compartment or spreads extrasphincterically. Intrasphincteric fistulas include both central and intersphincteric fistulas. The latter fistula, as well as the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 7 publications
0
69
0
1
Order By: Relevance
“…As all of the pelvic floor muscles except the LA arise fiom the PR, as has been proved both anatomically [5,6] and physiologically [7], stimulation of each individual muscle effects contraction of the other muscles by direct stimulation as well as by stimulation of sensory and motor fibers of the pudendal nerve, which lie in the muscle. Stimulation of the motor fibers of the pudendal nerve induces muscle contraction only of the stimulated muscle; meanwhile, stimulation of sensory fibers of the pudendal nerve induces reflex contraction of not only the stimulated muscle but also of all of the muscles supplied by the pudendal nerve, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As all of the pelvic floor muscles except the LA arise fiom the PR, as has been proved both anatomically [5,6] and physiologically [7], stimulation of each individual muscle effects contraction of the other muscles by direct stimulation as well as by stimulation of sensory and motor fibers of the pudendal nerve, which lie in the muscle. Stimulation of the motor fibers of the pudendal nerve induces muscle contraction only of the stimulated muscle; meanwhile, stimulation of sensory fibers of the pudendal nerve induces reflex contraction of not only the stimulated muscle but also of all of the muscles supplied by the pudendal nerve, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated both anatomically [5,6] and physiologically [7] that the puborectalis muscle (PR) gives rise to the external anal (EAS) and urethral (EUS) sphincters ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations